Western civilization - Spielvogel, Jackson J. , 1939- (Cengage Learning, 2015)
Includes 155 maps and excerpts of more than 250 primary sources that enliven the past while introducing students to the source material of historical scholarship. This text is illustrated with 430 photographs that add visual context